A facile strategy for high performance recyclable polymer systems via dynamic metal ion crosslinking. Issue 8 (8th February 2019) - Wang, Yanjun; Liu, Zhimeng; Zhou, Changlin; Yuan, Ye; Jiang, Liang; Wu, Bo; Lei, Jingxin
Abstract : Incorporation of pendant carboxyl during the synthesis process and reactive processing can be adopted to prepare high performance recyclable polymer systems. Abstract : A facile strategy of incorporating dynamic carboxylic zinc ion interactions into traditional linear polymers was developed to achieve the recyclability of crosslinked polymers. For newly synthesized polymers, pendant carboxyl can be incorporated into polymer chains during the synthesis process and subsequently crosslinked with zinc acetate. For commercial thermoplastics with only C–C bonds in the backbone, reactive processing offers an alternative approach to prepare vitrimers. This strategy is expected to be an effective approach for high performance recyclable polymer systems.